EXERCISES DESIGNED TO GROW THE ORAL AND WRITTEN SPEECH OF STUDENTS - Turanazarova Nilufar Raxmonqul qizi; Saydullayeva Shaxzoda (CONFERENCE OF NATURAL AND APPLIED SCIENCES IN SCIENTIFIC INNOVATIVE RESEARCH, 2024)
This article talks about teaching students to practice the specific features of the conditions and procedures for the use of exercises and methods designed to develop oral and written speech based on theoretical information